Dog team pulling a cart, ca. 1898 - Hegg, Eric A., 1867-1948
After the snow melted in the spring, dog teams didn't rest. They continued to work, pulling carts instead of sleds. This photo shows a team of six dogs pulling a cart loaded with a trunk and other supplies, possibly belonging to the woman standing near the cart (left center). Eric Hegg took this photo in Dawson sometime around 1898. Original title: Dog team express at Dawson City 1 photographic print mounted on cardboard: b&w; 16 x 21 cm.